2020
DOI: 10.14421/jsr.v15i1.1980
|View full text |Cite
|
Sign up to set email alerts
|

Capaian Unggahan Konten Akun Instagram Gembira Loka Zoo (Glzoo) Yogyakarta Terhadap Online Engagement Pada Masa Pandemi Covid-19

Abstract: The tourism sector is one of the sectors that was hardest hit when the Covid-19 pandemic hit Indonesia. Tourist visits during the Covid-19 pandemic decreased dramatically. To overcome this situation, serious efforts are needed to keep tourist destinations in demand by visitors, including the case study of Gembira Loka Zoo (GLZoo) Yogyakarta. One of the efforts taken by GLZoo managers is through social media, such as Instagram, in order to maintain the brand awareness of GLZoo as a tourist destination. Tourist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…The findings show that posted Instagram content shows the beauty of color photos that unconsciously trigger Generation Y and Z tourists to come to these tourist destinations. The argument of previous research by Fithriya (2020) explains that the character length of Instagram content captions is less able to be a reference as to whether it affects engagement achievements. However, this research found a fundamental difference.…”
Section: Discussionmentioning
confidence: 93%
“…The findings show that posted Instagram content shows the beauty of color photos that unconsciously trigger Generation Y and Z tourists to come to these tourist destinations. The argument of previous research by Fithriya (2020) explains that the character length of Instagram content captions is less able to be a reference as to whether it affects engagement achievements. However, this research found a fundamental difference.…”
Section: Discussionmentioning
confidence: 93%
“…Picture 3. Interactions on @pointcoffeid Through the comments feature, Instagram users can provide feedback or related questions post from @pointcoffee.id, @pointcoffee.id responded well and interactively to each comment (Aripradono, 2020;Fithriya, 2020). Every question is answered in a friendly manner even with emotions conveyed through emoticons.…”
Section: Discussionmentioning
confidence: 99%
“…Adapun penjualan dari instagram tidak terlalu signifikan karena target pasar tidak terlalu sesuai jika dibandingkan dengan penggunanya yang kebanyakan anak muda. Pemeliharaan konten Instagram juga menjadi hal penting untuk menjaga brand awareness di benak konsumen (Fithriya, 2020)…”
Section: Analisis Penggunaan Media Sosialunclassified